An environmentally friendly material for red tide algae removal: Performance and mechanism - Liu, Zhengyu; Yu, Zhiming; Cao, Xihua; Jiang, Wenbin; Yuan, Yongquan; Song, Xiuxian (Frontiers in Marine Science, 2022)
Red tide is a kind of marine disaster caused by the accumulation or proliferation of microalgae and other organisms in a short period of time, and utilizing modified clay to control and inhibit red tide is the preferred method. Among them, the application potential of organic-modified clay is high; unlike inorganic and microbial modifications, it has a broad-spectrum removal capacity on red tide algae at extremely low dosages. However, it has some disadvantages such as severe toxicity and high residual turbidity, leading to several limitations in its practical application. Therefore, it has become urgent to select organic-modified reagents with higher efficiency, weaker toxicity and lower residual turbidity. In this study, the typical red tide alga——Prorocentrum donghaiense was selected to detect the removal capacity of Polydimethyl diallyl ammonium chloride (PDMDAAC) modified clay (MP) by comparing with the Hexadecyl trimethyl ammonium bromide (HDTMA) modified clay (MH). Not only the physiological stress and flocculation effects of two modified clays on microalgae had been discussed, but also the properties of the modified clays had been characterized in this study. The results showed that the low degree of oxidative stress and less damage to the cell membrane make MP more environmentally friendly, PDMDAAC can remove microalgae at a low dose (2 mg/L) and quickly clarify the water by significantly enhancing the flocculation capacity of clay. In addition to discussing the removal mechanism of two modified clays on microalgae, schematic diagrams of the pathways were drafted. This study will provide support for the development of organic-modified clay.